Antibacterial, cytotoxicity and metabolite profiling of crude methanolic extract from andaliman (Zanthoxylum acanthopodium) fruit - Mada Triandala Sibero; ANGGUN PUSPITARINI SISWANTO; RETNO MURWANI; EVAN HANSEL FREDERICK; ALDI PRATAMA WIJAYA; EMMY SYAFITRI; KINDI FARABI; SHUN SAITO; YASUHIRO IGARASHI (Society for Indonesian Biodiversity, 2020)
Abstract. Sibero MT, Siswanto AP, Frederick EH, Wijaya AP, Syafitri E, Farabi K, Murwani R, Saito S, Igaras Y. 2020. Antibacterial, cytotoxicity and metabolite profiling of crude methanolic extract from andaliman (Zanthoxylum acanthopodium) fruit. Biodiversitas 21: 4147-4154. The local community in North Sumatra has utilized andaliman fruit (Zanthoxylum acanthopodium) as spices for traditional cuisines because it has a unique flavor. Information on the antimicrobial activity of Z. acanthopodium fruit against aquaculture pathogens and its bioactivity against leukemia cell lines are limited. The purposes of this study were to evaluate the antimicrobial activity of Z. acanthopodium fruit against Tenacibaculum maritimum, Vibrio alginolyticus, V. anguillarum, V. harveyi that are known as pathogens in aquaculture; to determine cytotoxic property against murine P388 leukemia cells; and to characterize its metabolites profile. The sample was extracted using methanol by the maceration method. Antibacterial assay was conducted by Kirby-Bauer disc diffusion method; while cytotoxicity assay using the XTT method. Proximate analysis showed that Z. acanthopodium fruit contained 63.41% of moisture, 24.73% of crude fiber, 9.81% of crude protein, 6.90% of ash, and 2.55% of crude fat. Several phytochemical components were detected, such as alkaloid, flavonoid, tannin, triterpenoid, and steroid. The GC/MS analysis indicated the presence of various compounds from terpenoid and terpenes derivatives. This study indicated that Z. acanthopodium fruit was not potential as antibacterial agents against the aquaculture pathogens; however, the methanol extract showed cytotoxic potential with IC50 19.14 µg/mL against murine P388 leukemia cells.